1999
DOI: 10.1103/physrevlett.83.3713
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity in FerromagneticRuSr2GdCu2O8

Abstract: Relying on the inhomogeneous (layered) crystal, electronic, and magnetic structure, we show how superconductivity can coexist with the ferromagnetic phase of RuSr2GdCu2O8 as observed by Tallon and coworkers. Since the Cu d x 2 −y 2 orbitals couple only to apical O px, py orbitals (and only weakly), which also couple only weakly to the magnetic Ru t2g orbitals, there is sufficiently weak exchange splitting, especially of the symmetric CuO2 bilayer Fermi surface, to allow singlet pairing. The exchange splitting … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
113
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(117 citation statements)
references
References 29 publications
4
113
0
Order By: Relevance
“…Some reports have concluded that the magnetic order in RuSr 2 RCu 2 O 8 is ferromagnetic in the RuO 2 layers [3][4][5][6]9,10,13] in which case there should be a competition between the superconducting and magnetic order parameters possibly resulting in a spontaneous vortex phase or a spatial modulation of the respective order parameters [7]. However, powder neutron diffraction studies on RuSr 2 GdCu 2 O 8 and RuSr 2 YCu 2 O 8 showed that the low-field magnetic order is predominately antiferromagnetic (~1 µ B /Ru) and there is a spin-flop transition that gradually occurs for magnetic fields greater than 0.4 T [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some reports have concluded that the magnetic order in RuSr 2 RCu 2 O 8 is ferromagnetic in the RuO 2 layers [3][4][5][6]9,10,13] in which case there should be a competition between the superconducting and magnetic order parameters possibly resulting in a spontaneous vortex phase or a spatial modulation of the respective order parameters [7]. However, powder neutron diffraction studies on RuSr 2 GdCu 2 O 8 and RuSr 2 YCu 2 O 8 showed that the low-field magnetic order is predominately antiferromagnetic (~1 µ B /Ru) and there is a spin-flop transition that gradually occurs for magnetic fields greater than 0.4 T [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…There have been a number of reports of the coexistence of magnetic order and superconductivity in the ruthenate-cuprates, RuSr 2 R 2-x Ce x Cu 2 O 10+δ and RuSr 2 RCu 2 O 8 where R is Gd, Eu or Y [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. These compounds were first synthesized by Bauernfeind, Widder and Braun [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is supported by symmetry considerations and band-structure calculations. 6 We propose that the electronic structure of the RuO 2 planes can be described by an effective double exchange model, with one localized spin at each site representing the Ru +5 ions, and additional n itinerant electrons per Ru coupled ferromagnetically with the localized spins.The model is the two-dimensional (2D) version of one widely used in manganites:Here S i is the localized spin operator representing the Ru +5 ion at site i, c † iσ is the operator creating an itinerant electron of spin σ at this site, and s i = αβ c † iα σ αβ c iβ gives the spin of this electron. For simplicity we take the Hund coupling, J H → +∞.…”
mentioning
confidence: 99%
“…This is supported by symmetry considerations and band-structure calculations. 6 We propose that the electronic structure of the RuO 2 planes can be described by an effective double exchange model, with one localized spin at each site representing the Ru +5 ions, and additional n itinerant electrons per Ru coupled ferromagnetically with the localized spins.…”
mentioning
confidence: 99%